PEMULIAAN (BREEDING) ASAS-ASAS HUKUM PERJANJIAN DALAM PERJANJIAN LEASING DI INDONESIA - Malikhatun Badriyah, Siti (Yustisia, 2012)
AbstractLeasing agreement is extremely useful for society, but there are many deviations from the principles of contract law and the principles of leasing in actual practices, so that is needed to make the breeding of the principles contract law. In the leasing agreement practice, there are some deviations from the principles of contract law and the leasing principles, so that they create inbalancing in the legal  relations;  the breeding of contract law principles becomes an important  thing which must be done immediatly in order to have a fair and balancing legal relations; the principle of contract law as the result of breeding is the harmony principle as prismatic principles of contract. The harmony principles  that integrated of the principle of  the reasonableness/equity, laras, rukun, the balancing and the proportionality.Key Word: breeding, the principle of contract law, financial, leasing